Characterization, Manipulation, and Isolation of Paramecium aurelia Using a Micro‐Electromigration Chip and Computer Vision. Issue 8 (3rd June 2020) - Shunmugam, Ashaa Preyadharishini; Fernandez, Javier G.
Abstract: Manipulating microorganisms with inherent motility is a challenging yet significant aim with implications in many biological, environmental, and technological applications. Many microorganisms that are broadly available in nature can be used as self‐powered systems that can be directed with external stimuli. Paramecium is a unicellular protozoan that exhibits a negative galvanotaxis where the cell follows the direction of weak electric fields. Here, the galvanotactic behavior of Paramecia is studied to achieve the precise manipulation of these organisms. Using a specially devised microfluidic chip and computer vision, unprecedented levels of manipulation and isolation of Paramecia are demonstrated, enabling their integration, use, and study in micro‐electromechanical systems. Abstract : Many microorganisms in nature can be used as selfpowered systems directed with external stimuli. This communication focuses on the use of the galvanotactic behavior of Paramecia to achieve the precise manipulation of these organisms. Using a specially devised microfluidic chip and computer vision, manipulation and isolation of Paramecia is demonstrated, enabling their integration, use, and study in micro‐electromechanical systems.